WEBSITE PLANNING SECOND MOTOR CREDIT ONLINE USING MACROMEDIA DREAMWEAVER 8 IN PT. ADIRA DINAMIKA MULTI FINANCE - Ahmad Fauzi; Marzuki, SKom, MMSI Marzuki, SKom, MMSI (Jurnal Sistem Informasi, 2007)
Second Motor Credit Campaign is performed through a variety of communications media, but has not been done through the website, the author feels like trying to make a second motor credit website online. This website  contains brief profiles of the Second Motor Credit. There are also administrators and consumers to input data and input data that manufacture motor using PHP and MySQL software. With this website, visitors and PT. FINANCE can provide or obtain necessary information, are also expected to promote second motor credit among visitors.